Navigating the mesentery: a comparative pre‐ and per‐operative visualization of the vascular anatomy. (September 2015) - Nesgaard, J. M.; Stimec, B. V.; Bakka, A. O.; Edwin, B.; Ignjatovic, D.; The RCC study group; Oresland, Tom; Færden, Arne Engebreth; Thorsen, Yngve; Andersen, Solveig; Negaard, Anne; Dicko, Aly; et al.
Abstract Aim Awareness of anatomy is critical for performing safe surgery within the root of the mesentery. Our aim was to investigate the anatomical relationship between the superior mesenteric artery (SMA) and vein (SMV) and their branches within a predefined D3 area of the right colon and to compare preoperatively established three‐dimensional (3D) mesenteric vessel anatomy from CT with that found at surgery. Method Prospective data were collected on 139 patients included in the 'Safe Radical D3 Right Hemicolectomy for Cancer Through Preoperative Biphasic Multi‐detector Computed Tomography (MDCT) Angiography' trial. CT data sets were 3D reconstructed before surgery and compared with photographs taken during the operation. Results The ileocolic artery was present and correctly identified in all patients and crossed the SMV anteriorly in 58 (41.7%). Seventeen patients had a right colic artery at surgery and there were three false‐negative and one false‐positive CT findings, yielding a diagnostic accuracy of 97.1%, sensitivity of 85.7% and specificity of 95.2%. Positive and negative predictive values were 94.7% and 97.5%, respectively. The middle colic artery was absent in one (0.7%) patient and multiple (nine double and one triple) in 10 (7.2%) patients. A mean of 3.8 ± 1.2 jejunal arteries and 2.0 ± 0.8 jejunal veins arose from the SMA and SMV. Jejunal veins crossed the SMA in the D3 area anteriorly in 30.9% of patients. In 26 (18.7%) patients, additional veins drained into the SMV, including pancreaticoduodenal in 16, right colic in six and both in two. The inferior mesenteric vein entered the SMV in 58 (41.7%) patients and crossed the D3 area in three (2.2%). Conclusion CT‐reconstructed anatomy has high specificity, sensitivity, accuracy and reliability.